Polymer size affects biodistribution and placental accumulation of the drug delivery biopolymer elastin-like polypeptide in a rodent pregnancy model. (December 2018) - Kuna, Marija; Waller, Jamarius P.; Logue, Omar C.; Bidwell, Gene L.
Abstract: Introduction: Fusion of therapeutic agents to Elastin-like Polypeptide (ELP) is a novel drug delivery strategy for prevention of placental drug transfer. Previous studies have used a 60 kDa ELP tag for this purpose. However, placental transfer of ELP may be size dependent. The goal of this study was to measure the effects of ELP polymer size on pharmacokinetics, biodistribution, and placental transfer of ELP. Methods: Three ELPs ranging from 25 to 86 kDa (4.1–6.8 nm hydrodynamic radius) were fluorescently labeled and administered by i.v. bolus to pregnant Sprague Dawley rats on gestational day 14. Plasma levels were monitored for 4 h, organ levels and placental transfer determined by ex vivo fluorescence imaging, and placental localization determined by confocal microscopy. Results: Increasing ELP size resulted in slower plasma clearance and increased deposition in all major maternal organs, except in the kidneys where an opposite effect was observed. Placental levels increased with an increase in size, while in the pups, little to no ELP was detected. Discussion: Pharmacokinetics and biodistribution of ELPs during pregnancy are size dependent, but all ELPs tested were too large to traverse the placental barrier. These studies verify that ELP fusion is a powerful method of modulating half-life and preventing placental transfer of cargo molecules. The tunable nature of the ELP sequence makes it ideal for drug delivery applications during pregnancy, where it can be used to target drugs to the mother while preventing fetal drug exposure. Highlights: Increase in ELP size results in slower plasma clearance in rodent pregnancy model. Kidney ELP levels decrease with an increase in ELP size. Increase in ELP size increases their placental accumulation. There is no placental transfer regardless of the change in ELP size.